Mapping the Evolution of Constructivist Pedagogy: VOSviewer Visualization of Inter-disciplinary Applications, E-Learning Shifts, and Geographic Research Dominance - Priandani, Ai Pemi; Riyana, Cepi; Emilzoli, Mario; Alharir, Gamal Adam; Aruan, Juwintar Febriani (Universitas Muhammadiyah Surakarta, 2025)
10 year research trend of constructivism in modern education is the main goal of this research. Scientific publication data taken from the Scopus database is analyzed using VOSviewer software to visualize networks, overlays, and density visualizations. The results of the study show that constructivism remains an important cornerstone in the development of modern education, shown by a significant increase in the number of publications. The United States dominated research production, followed by China showing increased attention to constructivism. Social Sciences is the field that applies constructivism the most, but other fields such as Arts and Humanities, Engineering, and Computer Science also show significant contributions. The analysis of keyword co-occurrence revealed several important trends, including an increased focus on technology integration (e-learning, modern technologies), the development of a learning environment that supports constructivism, and attention to student learning strategies. Overlay visualization shows the shift in research focus over time, while density view shows the intensity of research on specific topics. The conclusion of this study is that constructivism remains a relevant and dynamic approach in modern education. This research provides a comprehensive overview of the development of constructivism research and can be the foundation for further research that is more in-depth and specific.